Chronic rheumatic heart disease with recrudescence of acute rheumatic fever on histology: a case report. Issue 7 (5th July 2022) - Mutithu, Daniel W; Roberts, Riyaadh; Manganyi, Rodgers; Ntusi, Ntobeko A B
Abstract: Background: Rheumatic heart disease (RHD) is endemic in sub-Saharan Africa where it is the leading cause of cardiovascular mortality in the young. Rheumatic heart disease results from recurrent episodes of acute rheumatic fever (ARF), which are often difficult to diagnose clinically. Acute rheumatic fever may be diagnosed based on the revised Jones Criteria 2015 for the diagnosis of ARF. Histologically, acute rheumatic valvulitis manifests with active inflammation characterized by lymphocytic infiltration, Aschoff bodies, and Anitschkow cells. Chronic rheumatic valvulitis is associated with neovascularization, and/or dystrophic calcification. The combination of histological features of both ARF and chronic RHD is a rare finding. Case summary: Here we report on a case of a 59-year-old woman with mixed aortic and mitral valve disease of probable rheumatic aetiology (elevated C-reactive protein and prolonged PR interval) and with histological evidence of lymphocytic infiltration, Aschoff bodies, and fibrinoid necrosis admixed with features of chronic RHD. Discussion: Cases of chronic RHD admixed with ARF are very rare; however, they should be considered in regions with a high prevalence of RHDs.